Kinerja Manajerial di Universitas Negeri Manado Dalam Hal Implementasi Sistem Pengendalian Intern dan Komitmen Organisasi - Cecilia Lelly Kewo (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
This research examines the internal control system implementation and organizational commitment effects on managerial performance at Universitas Negeri Manado empirically. This research uses the descriptive quantitative method, while the analysis method uses descriptive analysis. This research uses primary data by collecting research instruments in questionnaires, observation, and interviews. The target population is the management and staff of Universitas Negeri Manado. The sampling method using simple random sampling and the number of questionnaires that meet the processed requirements is 75 questionnaires. This research uses IBM SPSS Statistics software to test the collected data. Hypothesis testing uses the path analysis method. This research shows that internal control system implementation has a significant positive effect on managerial performance. Likewise, organizational commitment partially has a positive effect on managerial performance. Overall, internal control system implementation and organizational commitment positively and significantly affect managerial performance at Universitas Negeri Manado.